2020
DOI: 10.1002/cre2.256
|View full text |Cite
|
Sign up to set email alerts
|

A proof‐of‐principle bite force study using two experimental test denture adhesives and a currently marketed denture adhesive

Abstract: Objectives This proof‐of‐principle, single‐center, randomized, examiner‐blind, crossover study compared two experimental polyvinyl acetate (PVA)‐based denture adhesives (Test Adhesives 1 and 2) with a marketed reference polymethyl vinyl ether/maleic anhydride (PMV/MA)‐based adhesive and no adhesive using incisal bite force area over baseline over 12 hr (AOB0–12) in participants with an at least moderately well‐fitting complete maxillary denture. Previous in vitro studies suggested the experimental denture adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The retention of complete dentures depends on the the interaction of various physical mechanisms, including adaptation to the supporting tissues, the presence of thin film of saliva between the intaglio of the denture and tissues, adequate peripheral edge extension, and atmospheric pressure [ 11 , 12 ]. However, this retention can suffer due to alterations in both hard and soft tissues, declines in saliva consistency and volume due to age or medication, and changes in neuromuscular control [ 10 , 12 , 13 ]. Among the available options to enhance retention and stability of complete dentures are denture adhesives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retention of complete dentures depends on the the interaction of various physical mechanisms, including adaptation to the supporting tissues, the presence of thin film of saliva between the intaglio of the denture and tissues, adequate peripheral edge extension, and atmospheric pressure [ 11 , 12 ]. However, this retention can suffer due to alterations in both hard and soft tissues, declines in saliva consistency and volume due to age or medication, and changes in neuromuscular control [ 10 , 12 , 13 ]. Among the available options to enhance retention and stability of complete dentures are denture adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have consistently demonstrated that denture adhesives help improve the retention and stability of complete dentures, improving the quality of life and satisfaction of patients [ 2 , 4 , 11 , 13 , 15 , 16 , 18 21 ]. Their use has been linked to a reduction in the likelihood of tissue trauma and an improved ability to chew and speak effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum bite force [MBF] is a significant variable to evaluate oral function (5) .It additionally impacts diet selection, which has a vital role in the maintenance of masticatory activity (6)(7) . Old age people with missing teeth avoid a fibrous diet, which is considered an essential source of fibers, proteins, and vitamins (8)(9) .…”
Section: Introductionmentioning
confidence: 99%